LEARNING VOCABULARIES USING COLOURFUL CHALKS AS A MEDIA FOR FIFTH GRADE STUDENTS OF SDN PADANGSARI 01 SEMARANG - Cendrawasih Puspita Widiyaningrum (ETERNAL (English Teaching Journal), 2014)
The objevtives of the study are (1) to find out the ability of the fifth grade students of SDN Padangsari 01 Semarang in learning vocabulary before taught by using colorful chalks, (2) to know the students ability in learning vocabulary after using colorful chalks as a media, (3) to identify the effectiveness of using colorful chalks as a media of teaching vocabulary. To reach the objectives of the study, the writer used descriptive method. The population of this study is the fifth grade students of SDN Padangsari 01 Semarang. There are 20 students of the fifth grade students of SDN Padangsari 01 Semarang In this study the writer uses total sampling. The writer got the data from one way; there is test. The result of her observation show that; (1) The ability of the fifth grade students of SDN Padangsari 01 Semarang in learning vocabulary before using colorful chalks as a media is fair. It can be seen from 20 samples in the research. The specification is 12 students with fair criterion, 6 students with good criterion, and 2 students with very good criterion. So that, it can be said that there are 40% of the fifth grade students of SDN Padangsari 01 Semarang who are successful in learning vocabulary before using colorful chalks as a media. (2) The ability of the fifth grade students of SDN Padangsari 01 Semarang in learning vocabulary after using colorful chalks as a media is very good. It can be seen from 20 samples in the research. The specification is 17 students with very good criterion, 2 students with good criterion, and 1 student with fair criterion. So that, it can be said that there are 95% of the fifth grade students of SDN Padangsari 01 Semarang who are successful in learning vocabulary using colorful chalks as media. (3) The effectiveness of learning vocabulary using colorful chalks as media; After seen the result from the test which given by the writer, it can be classified that learning vocabulary using colorful chalks is effective.